Computer Use and Computer Anxiety in Older Korean Americans. (September 2016) - Yoon, Hyunwoo; Jang, Yuri; Xie, Bo
Responding to the limited literature on computer use in ethnic minority older populations, the present study examined predictors of computer use and computer anxiety in older Korean Americans. Separate regression models were estimated for computer use and computer anxiety with the common sets of predictors: (a) demographic variables (age, gender, marital status, and education), (b) physical health indicators (chronic conditions, functional disability, and self-rated health), and (c) sociocultural factors (acculturation and attitudes toward aging). Approximately 60% of the participants were computer-users, and they had significantly lower levels of computer anxiety than non-users. A higher likelihood of computer use and lower levels of computer anxiety were commonly observed among individuals with younger age, male gender, advanced education, more positive ratings of health, and higher levels of acculturation. In addition, positive attitudes toward aging were found to reduce computer anxiety. Findings provide implications for developing computer training and education programs for the target population.